background image

Transitivity.

Let

A ∼ B

and

B ∼ C

for some small f.o.

A

,

B

, and

C

. Then exist a set

X

such

that

X

up

A

and

X

up

B

and

P

X

up

A

=

P

X

up

B

and a set

Y

such that

Y

up

B

and

Y

up

C

and

P

Y

up

B

=

P

Y

up

C

. So

X

Y

up

A

because

P

Y

P

X

up

A

=

P

Y

P

X

up

B

=

P

(

X

Y

)

up

B ⊇ {

X

Y

} ∩

up

B ∋

X

Y .

Similarly we have

X

Y

up

C

. Finally

P

(

X

Y

)

up

A

=

P

Y

P

X

up

A

=

P

Y

P

X

up

B

=

P

X

P

Y

up

B

=

P

X

P

Y

up

C

=

P

(

X

Y

)

up

C

.

Definition 4.

The

rebase

A ÷

A

for a f.o.

A

and a set

A

(base) such that

X

up

A

:

X

A

is

defined by the formula

A ÷

A

=

up

1

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

where “up” is taken for the set of f.o. on

A

.

Proposition 5.

If

X

up

A

:

X

A

then:

1.

A ÷

A

is a f.o.

2.

A ÷

A

∼ A

.

Proof.

1. We need to prove that

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

is a filter. That it is an upper set

is obvious. It is non-empty because

Y

up

A

:

Y

A

and thus

A

∈ {

X

P

A

| ∃

Y

up

A

:

Y

X

}

. Let

P , Q

∈ {

X

P

A

| ∃

Y

up

A

:

Y

X

}

. Then

P , Q

A

and

P

up

A

:

P

P

and

Q

up

A

:

Q

P

. So

P

Q

A

and

P

Q

P

Q

. Thus

P

Q

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

.

2.

P

(

A

S

up

A

)

up

A

=

up

(

A ÷

(

A

S

up

A

)) =

{

X

P

(

A

S

up

A

)

| ∃

Y

up

A

:

Y

X

}

=

P

(

A

S

up

A

)

up

A

=

P

A

up

A

=

{

X

P

A

|

X

up

A}

=

{

X

P

A

| ∃

Y

up

A

:

Y

X , X

S

up

A}

=

{

X

P

A

| ∃

Y

up

A

:

Y

X ,

X

A

S

up

A}

=

P

(

A

S

up

A

)

up

(

A ÷

A

)

.

Thus

A ÷

A

∼ A

because

A

S

up

A ⊇

X

S

up

A

=

X

up

A

for some

X

up

A

and

A

S

up

A ⊇

X

S

up

A ∈ {

X

P

A

| ∃

Y

up

A

:

Y

X

}

=

up

(

A ÷

A

)

.

Proposition 6.

A

up

A ⇒

up

(

A ÷

A

) =

P

A

up

A

.

Proof.

Let

A

up

A

. Then up

(

A ÷

A

) =

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

=

{

X

P

A

|

X

up

A}

=

P

A

up

A

.

Lemma 7.

If

A ∼ B

then

Y

up

A

:

Y

X

⇔ ∃

Y

up

B

:

Y

X

for every f.o.

A

,

B

, and a set

X

.

Proof.

We will prove

Y

up

A

:

Y

X

⇒ ∃

Y

up

B

:

Y

X

(the other direction is similar).

We have

P

K

up

A

=

P

K

up

B

for some set

K

.

Y

up

A

:

Y

X

⇒ ∃

Y

P

K

up

A

:

Y

X

⇒ ∃

Y

P

K

up

B

:

Y

X

⇒ ∃

Y

up

B

:

Y

X

.

Proposition 8.

If

A ∼ B

then

B

=

A ÷

S

up

B

for every f.o.

A

,

B

.

Proof.

P

Y

up

A

=

P

Y

up

B

for some set

Y

up

A

,

Y

up

B

. Thus exists a set

X

up

A

such

that

X

up

B ⊆

S

up

B

. Thus

X

up

A

:

X

S

up

B

and so

A ÷

S

up

B

is a properly defined f.o.

X

up

(

A ÷

S

up

B

)

X

P

S

up

B ∧ ∃

Y

up

A

:

Y

X

X

P

S

up

B ∧ ∃

Y

up

B

:

Y

X

X

up

B

(the lemma used).

2.2 Trans-reloids

Definition 9.

A

trans-reloid

is a f.o. on the set

A

×

B

for some small sets

A

and

B

.

I will denote the set of trans-reloids for sets

A

,

B

as

RLD

(

A

;

B

)

.

Definition 10.

Src

f

=

S

Pr

0

up

f

; Dst

f

=

S

Pr

1

up

f

for every trans-reloid

f

.

2

Section 2